OPTIMIZATION OF TOTAL SOLUBLE PROTEIN OF YOGHURT WITH ADDITION OF PSYLLIUM HUSK POWDER AND FULL CREAM MILK POWDER - SAFRI ISHMAYANA; MUHAMMAD FADHLILLAH; FAJRIANA S. NURRUSYDA; AGUS SAFARI; RIZA APRIANI; PUSPITASARI R. DEVI; DEBORA T. HORASIO; UKUN M. S. SOEDJANAATMADJA (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Yoghurt is a fermented dairy product with many beneficial properties. During fermentation process using lactic acid bacteria, the physicochemical properties of yoghurt change including the soluble protein (SP) content due to the formation of insoluble protein as a result of decreasing pH. The present study was directed to determine the best conditions to obtain the highest SP content, even though some of proteins become insoluble in yoghurt. The optimal conditions were determined by response surface method-central composite design (RSM-CCD). Yoghurt was prepared by fermenting pasteurized milk with Lactobacillus bulgaricus with varying concentrations of psyllium husk powder (PHP) and full cream milk powder (FCMP). The SP content was determined using Lowry method. The results of the present study indicate that the highest SP content can be achieved when 0.162 % w/v PHP and 5.621 % w/v FCMP are used in the yoghurt preparation process. The SP concentration at these conditions can reach up to 2.704 ± 0.102 mg·mL-1. The organoleptic tests of the yoghurt indicate that it has better acceptance by semi-trained panelists compared to yoghurt prepared without the addition of PHP and FCMP.